KARAKTERISTIK PENDERITA KANKER PAYUDARA YANG DIRAWAT INAP DI RS St. ELISABETH MEDAN TAHUN 2011-2013 - LESTARI ESTARIA SINAGA; Sori Muda Sarumpaet; Rasmaliah . (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2014)
ABSTRACT Breast cancer is carcinoma derived from ducts or labullus. Breast cancer is a global problem and the leading cause of death in women in the world. Breast cancer ranks second of all cancers in women with a prevalence rate of 56.5 per 100,000 women in the world. The prevalence of breast cancer in Indonesia is 46.3 per 100,000 women. Data from medical record of of St. Elisabeth general hospital Medan in 2011-2013 there were 102 cases of breast cancer which hospitalized. This research aims to know characteristics of hospitalized patients with breast cancer in St. Elisabeth hospital Medan in 2011-2013. This research is a descriptive case series design. The study was conducted at the Hospital of St. Elisabeth Medan from March to October, 2014. Population and sample totaled as 102 people (total sampling). Data obstained medical records, data analyzed by Chi-square test and Mann Whitney. The results show the highest proportion of breast cancer patients are ages > 40 years (81,4%), women (100%), Bataknese (64,7%), Christians (52,0%), not working (52,9%), married (97,1%), residence outside the field of Medan (56,9%), the main complaintment of lumps and pain in breast (74,5%), stage III (49,0%), lies on the left breast (52,0%), surgery (56,9%), length of treatment on average 6,85 days, home ambulatory (84,3%). The results of statistical tests improve there is no difference between age based on clinical stage (p = 0,150), average length of treatment with clinical stage (p = 0,866) average treatment time - flat with the type of medical management (p = 0,204). There is a difference between the clinical stagewith the type of medical management (p = 0,000) and the clinical stage based on the chief complaint (p = 0,001).Women are advised to perform breast self-examination and encoraged a self-defined to the health service if it is encountered a lump in breast/axilla area.